Global nitrous oxide emissions from livestock manure during 1890–2020: An IPCC tier 2 inventory - Lei Zhang; Shufen Pan; Zhiyun Ouyang; Josep G. Canadell; Jinfeng Chang; Giulia Conchedda; Eric A. Davidson; Fei Lu; Naiqing Pan; Xiaoyu Qin; Hao Shi; Francesco N. Tubiello; et al. (Global Change Biology, 2024)
Nitrous oxide (N 2 O) emissions from livestock manure contribute significantly to the growth of atmospheric N 2 O, a powerful greenhouse gas and dominant ozone‐depleting substance. Here, we estimate global N 2 O emissions from livestock manure during 1890–2020 using the tier 2 approach of the 2019 Refinement to the 2006 IPCC Guidelines. Global N 2 O emissions from livestock manure increased by ~350% from 451 [368–556] Gg N year −1 in 1890 to 2042 [1677–2514] Gg N year −1 in 2020. These emissions contributed ~30% to the global anthropogenic N 2 O emissions in the decade 2010–2019. Cattle contributed the most (60%) to the increase, followed by poultry (19%), pigs (15%), and sheep and goats (6%). Regionally, South Asia, Africa, and Latin America dominated the growth in global emissions since the 1990s. Nationally, the largest emissions were found in India (329 Gg N year −1 ), followed by China (267 Gg N year −1 ), the United States (163 Gg N year −1 ), Brazil (129 Gg N year −1 ) and Pakistan (102 Gg N year −1 ) in the 2010s. We found a substantial impact of livestock productivity, specifically animal body weight and milk yield, on the emission trends. Furthermore, a large spread existed among different methodologies in estimates of global N 2 O emission from livestock manure, with our results 20%–25% lower than those based on the 2006 IPCC Guidelines. This study highlights the need for robust time‐variant model parameterization and continuous improvement of emissions factors to enhance the precision of emission inventories. Additionally, urgent mitigation is required, as all available inventories indicate a rapid increase in global N 2 O emissions from livestock manure in recent decades.

New estimates of greenhouse gas emissions from biomass burning and peat fires using MODIS Collection 6 burned areas - Paolo Prosperi; Mario Bloise; Francesco N. Tubiello; Giulia Conchedda; Simone Rossi; Luigi Boschetti; Mirella Salvatore; Martial Bernoux (Climatic Change, 2020)
The Paris Agreement calls on parties to undertake ambitious efforts to combat climate change by engaging in appropriate policies and measures as put forward through Nationally Determined Contributions (NDCs), to strengthen transparency when reporting their greenhouse gas (GHG) emissions and to increase their mitigation contributions to climate action from 2020. It also calls for regular and transparent monitoring and reporting of the GHG emissions and on the NDCs implementation efforts. Biomass fires significantly affect the GHG atmospheric balance, with fire emissions representing more than 5% of total emissions from agriculture, forestry, and other land use (AFOLU), according to recent estimates produced by the Food and Agriculture Organization (FAO). We update previously published Tier 1 estimates of GHG emissions in FAOSTAT—which had been used in the IPCC AR5 analysis—by using new burned area activity data from the Moderate Resolution Imaging Spectroradiometer (MODIS) known as MCD64A1, Collection 6. The previous FAOSTAT estimates had used as input the Global Fire Emission Database v.4 (GFED4) burned area product, based on older MODIS Collection 5.1 burned area product. In line with differences between the input data used, the new FAOSTAT estimates indicate roughly 30% higher fire emissions globally than previously published. Our analysis also confirms that the FAOSTAT Tier 1 approach produces fire emissions estimates that are comparable to those computed at Tier 3 by GFED, and thus represent a useful complementary tool in support of country GHG reporting.

Mapping global cropland and field size - Steffen Fritz; Linda See; Ian McCallum; Liangzhi You; Andriy Bun; Elena Moltchanova; Martina Duerauer; Fransizka Albrecht; Christian Schill; Christoph Perger; Petr Havlik; Aline Mosnier; et al. (Global Change Biology, 2015)
A new 1 km global IIASA ‐ IFPRI cropland percentage map for the baseline year 2005 has been developed which integrates a number of individual cropland maps at global to regional to national scales. The individual map products include existing global land cover maps such as GlobCover 2005 and MODIS v.5, regional maps such as AFRICOVER and national maps from mapping agencies and other organizations. The different products are ranked at the national level using crowdsourced data from Geo‐Wiki to create a map that reflects the likelihood of cropland. Calibration with national and subnational crop statistics was then undertaken to distribute the cropland within each country and subnational unit. The new IIASA ‐ IFPRI cropland product has been validated using very high‐resolution satellite imagery via Geo‐Wiki and has an overall accuracy of 82.4%. It has also been compared with the EarthStat cropland product and shows a lower root mean square error on an independent data set collected from Geo‐Wiki. The first ever global field size map was produced at the same resolution as the IIASA ‐ IFPRI cropland map based on interpolation of field size data collected via a Geo‐Wiki crowdsourcing campaign. A validation exercise of the global field size map revealed satisfactory agreement with control data, particularly given the relatively modest size of the field size data set used to create the map. Both are critical inputs to global agricultural monitoring in the frame of GEOGLAM and will serve the global land modelling and integrated assessment community, in particular for improving land use models that require baseline cropland information. These products are freely available for downloading from the http://cropland.geo-wiki.org website.